Lightweight, Heavy Lifting: Knowledge Flows and Technology Transfer in a Materials Technology Lab - Warrian, Peter; Najam, Ahmed (Journal of Management Policy and Practice, 2017)
This paper overviews the interaction of public research laboratories and SME firms. It overviews the key institutional features that enable effective public research laboratories and SME interaction, and it delineates examples of such interactions.